Communication and intersectoral collaboration for the dissemination of agricultural technology in Fujian Province, the People's Republic of China - Ziqi, Wang; Navarro, R. L.; Raab, R. T. (2001)
A case study was conducted in Fujian Province, the People’s Republic of China from 1998 to 1999 to answer the question “What mechanisms contribute to effective communication and intersectoral collaboration to disseminate agricultural technology in Fujian, China?” Through stratified simple random sampling, 338 survey respondents were selected and interviewed.

Intersectoral collaboration was realized through information sharing, non-information sharing, management sharing, and operations sharing. Supported by intersectoral collaboration, information was disseminated and technologies were promoted ultimately to farmers through various media: demo farm; adult education; training for farmers, technicians and demo households; instruction through correspondence; radio and TV broadcasts; cable TV information from rural trade associations; training members of the Youth League; and communication through the village committees.

China’s successful experience in communication and intersectoral collaboration for the dissemination of agricultural technology may help other developing countries as they confront problems related to food security and the alleviation of rural poverty. A three-way communication system model and a farmer-centered communication strategy are recommended.
Keywords: Agricultural development; Agricultural technology; Collaborative farming; Communication in community development; Community coordination; Community development -- Asia